Hormones and B-cell development in health and autoimmunity - Santana-Sánchez, Paola; Vaquero-García, Ricardo; Legorreta-Haquet, María Victoria; Chávez-Sánchez, Luis; Chávez-Rueda, Adriana Karina (Frontiers in Immunology, 2024)
The development of B cells into antibody-secreting plasma cells is central to the adaptive immune system as they induce protective and specific antibody responses against invading pathogens. Various studies have shown that, during this process, hormones can play important roles in the lymphopoiesis, activation, proliferation, and differentiation of B cells, and depending on the signal given by the receptor of each hormone, they can have a positive or negative effect. In autoimmune diseases, hormonal deregulation has been reported to be related to the survival, activation and/or differentiation of autoreactive clones of B cells, thus promoting the development of autoimmunity. Clinical manifestations of autoimmune diseases have been associated with estrogens, prolactin (PRL), and growth hormone (GH) levels. However, androgens, such as testosterone and progesterone (P4), could have a protective effect. The objective of this review is to highlight the links between different hormones and the immune response mediated by B cells in the etiopathogenesis of systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), and multiple sclerosis (MS). The data collected provide insights into the role of hormones in the cellular, molecular and/or epigenetic mechanisms that modulate the B-cell response in health and disease.